Rinaldo Bertolino e la scienza ecclesiasticistica. Note di presentazione - Fumagalli Carulli, Ombretta 1944- (2012)
Tribute to Renaldo Bertolino as a professor of Ecclesiastical Law. He has been at the same time precise in his work and inclined to self-questioning with a profound regard for the spiritual depth of human existence. The title of the book offered to him, Aequitas sive Deus, recalls the humility of his work
Keywords: Bertolino, Rinaldo -- 1940-; Kanonistik; Kirchenrecht; Praxis; Festschrift; Kirchenrechtslehrer